The Role of Laboratory Findings in Guiding Physiotherapy Treatment Plans: A Review - Alfaifi, Sami Yahya Jaber; Alqahtani , Turki Ali Salem; Alasmari, Abdulrahman Ali Mohammed; Al-Asmari, Saeed Mohammed Mohsen; Alshehri, Salem Ahmed Ali; Arishi, Abdulhakim Abdullah (Journal of Ecohumanism, 2024)
The integration of laboratory findings into physiotherapy treatment planning is a critical step toward personalized and evidence-based patient care. This review explores the role of laboratory diagnostics in guiding physiotherapy interventions, with a focus on key biomarkers such as inflammatory markers, metabolic indicators, and oxygenation levels. By synthesizing findings from recent studies, the review highlights how laboratory data can inform the intensity, type, and progression of physiotherapy, particularly in managing conditions like rheumatoid arthritis, diabetes, and pulmonary diseases. The evidence suggests that laboratory-guided physiotherapy not only enhances patient outcomes but also ensures safer and more effective rehabilitation. Challenges, including the accessibility of diagnostic tools and interdisciplinary collaboration, are discussed alongside recommendations for integrating laboratory findings into physiotherapy practice and education.